Conductive natural rubber/carbon black nanocomposites via cellulose nanowhisker templated assembly: tailored hierarchical structure leading to synergistic property enhancements1. Issue 25 (7th July 2015) - Wu, Xiaodong; Lu, Canhui; Zhang, Xinxing; Zhou, Zehang
<x xml:space="preserve">Abstract</x> Cellulose nanowhisker assisted fabrication of carbon black based 3D hierarchical conductive structures in natural rubber with enhanced performance.